Synthesis, Characterization and Antibacterial Activities of Ligand Type N2O4 Schiff base and its Novel Complexes with Co(II), Ni(II), Cu(II) and Zn(II) ions. - T. Numan, Ahmed; R. Aziz, Manhel; M. Shaker, Sinaa (Iraqi Journal of Pharmaceutical Sciences, 2017)
The reaction of 2-amino benzoic acid with 1,2-dichloroethane under reflux in methanol and KOH as a base to gave the precursor [H4L]. The precursor under reflux and drops of CH3COOH which reacted with (2mole) from salicycaldehyde in methanol to gave a new type N2O4 ligand [H2L], this ligand was reacted with (MCl2) Where [M= Co (II), Ni(II), Cu(II) and Zn(II)] in (1:1) ratio at reflux in methanol using KOH as a base, to give complexes of the general formula [M(L)]. All compounds have been characterized by spectroscopic methods [1H NMR ( just to the ligand), FTIR, uv-vis, atomic absorption], melting point, conductivity, chloride content, as well as magnetic susceptibility measurements. From the above data, the proposed molecular structure of [Co(L)], [Ni(L)], [Cu(L)] and[Zn(L)] complexes adopting an octahedral about this metal ions. The synthesized ligand, along with their metal complexes were screened for their in vitro antibacterial activity against ten local strains of E. coli as gram-negative bacteria in addition to ten strains of Salmonella typhi and to ten strains of Acinetobacter baumannii and Ten gram- positive bacteria utilizing for locally strains of Staphylococcus aureus, were tested also using the agar diffusion technique. Keywords: Schiff base , Complexes .